Our bodies The child's first library of learning - N/A (Time life Asia New York, 1996)
A Child's First Library of Learning: Our Bodies is an informative children$1 (Bs book that introduces young readers to the human body through a question-and-answer format. Each section addresses a specific body part or function$1 (Blike breathing, digestion, bones, or the five senses$1 (Bpaired with colorful illustrations and engaging facts. The book encourages curiosity and helps children understand how their bodies work in a fun and simple way. Abstract A Child's First Library of Learning: Our Bodies presents fundamental information about the human body in an engaging and educational manner suitable for children. Utilizing a structured question-and-answer format, the book explores various bodily systems and functions, promoting early scientific literacy. Accompanied by colorful visuals and supplementary facts, the book supports interactive learning and stimulates children's natural curiosity about how their bodies work. Review This book is a fantastic resource for young learners. Its Q&A structure makes it easy to follow and allows children to actively engage with the content. The illustrations are vibrant and detailed, helping to visualize complex systems in a child-friendly way. What sets it apart are the fun side facts, which make learning enjoyable and memorable. Whether used in a classroom or at home, this book is a great tool for introducing basic science concepts to children in an accessible and interactive format.s
The book is structured in a question-and-answer format, making complex topics approachable for children. Each section explores a different function or aspect of the human body, complemented by engaging illustrations and fun side facts.
shelf A ( A1)
This book is designed for young learners aged 5 to 10 years, making it ideal for early primary students from Kindergarten to Grade 4. It is suitable for: Children who are curious about how their bodies work Teachers looking for science resources that are age-appropriate and engaging Parents who want to introduce basic biology at home in a fun and interactive way School libraries seeking accessible nonfiction material for beginner readers Its simple language, question-based format, and vivid illustrations make it especially useful for visual learners and early readers who benefit from structured, interactive content.